2020
DOI: 10.1016/j.amsu.2020.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between BRAF V600E and KRAS mutations in stool for identifying colorectal cancer: A cross-sectional study

Abstract: Background With early diagnosis, colorectal cancer (CRC) is a curable disease. As studies in the past 15 years have shown, specific genetic changes occur in the neoplastic transformation of normal colonic epithelium to benign adenoma until becoming adenocarcinoma. Considering that dynamic, we aimed to determine how v-raf murine sarcoma viral oncogene homolog B1 (BRAF) V600E and Kirsten rat sarcoma (KRAS) mutations relate to the location, histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Difference results were also found in the study conducted in Mexico, Latin America and the Caribbean population, which was 4% and 7.8%, respectively (Hernández-Sandoval et al 2020). Meanwhile, different results were also found in Indonesia, showing BRAF V600E mutation in 6 (14%) of 43 samples (Warsinggih et al 2020) and another study identified no BRAF mutation (Ni Nyoman et al 2020). Another mutation of BRAF non-V600E was found in this study, with a change in a valine (GTG) to leucine (TTG) or known as V600L.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Difference results were also found in the study conducted in Mexico, Latin America and the Caribbean population, which was 4% and 7.8%, respectively (Hernández-Sandoval et al 2020). Meanwhile, different results were also found in Indonesia, showing BRAF V600E mutation in 6 (14%) of 43 samples (Warsinggih et al 2020) and another study identified no BRAF mutation (Ni Nyoman et al 2020). Another mutation of BRAF non-V600E was found in this study, with a change in a valine (GTG) to leucine (TTG) or known as V600L.…”
Section: Discussionmentioning
confidence: 76%
“…The absence of population-based data in Indonesia leads to an unclear overview of the incidence of CRC. Various reports show increases in the number of cases of CRC as one of the ten most common cancers (Warsinggih et al 2020). These indicate that colorectal cancer is one of the concerned health problem.…”
Section: Introductionmentioning
confidence: 99%
“…The other aliquot was tested for CRP serum level on the day of sampling, namely with an ELISA kit (reference no. CAN-CRP-4360) from Diagnostics Biochem Canada Inc. (Ontario, Canada) according to the manufacturer's instructions [ [15] , [16] , [17] ]. Measurements of IL-6 concentration were expressed in picograms per milliliter (pg/mL) and of CRP serum level in milligrams per liter (mg/L).…”
Section: Methodsmentioning
confidence: 99%